PENGARUH LATIHAN DRIBBLE TERHADAP KETERAMPILAN MENGGIRING BOLA PADA SISWA EKSTRAKURIKULER SEPAKBOLA SMA NEGERI 8 PEKANBARU - Fitradha, Revanno; ', Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of the research is that the students of SMA Negeri 8 Pekanbaru who join in football extracurricular are still having a bad dribble ability, whether in practice or in a match. It can be seen clearly in a match when the ball is easily snatched away by the opponent, losing control in ball’s mastery, too hard to break through opponent’s defense, and application of dribble exercise which is too variety given by the coach. The form of the research is a research with experimental treatment. The population in this research is the students of football extracurriculer of SMA Negeri 8 Pekanbaru, the sample of this research is the entire population which is 18 people. The data collection technique is derived from the pre-test and post-test. The instrument used in this research is dribble test, which aims to measure the ability to dribble. The variables of this research are dribble practice which denoted by X as an independent variable, whereas the ability of dribble is denoted by Y as a dependent variable. After that, the data are processed statistically, to test the normality with liliefors test, at 0,05 significance level .The hypothesis that submitted is the existence of the effects of dribble exercise of ability to dribble. The result of pre-test and post-test in the analysis using uji-t, the result of uji-t shows that thitung in amount of 3,500 with ttabel is 1,74, then H_a at alpha level is 0,05. It can be concluded that there is a significant effects of dribble exercise of dribble ability of football extracurriculer students of SMA Negeri 8 Pekanbaru.Key Words: dribble exercise